Autonomous group particle swarm optimisation tuned dynamic voltage restorers for improved fault‐ride‐through capability of DFIGs in wind energy conversion system. Issue 4 (1st December 2020) - Swain, Snehaprava; Ray, Pravat Kumar
Abstract : In this paper, a multi‐objective tuning algorithm is proposed for the voltage/current controllers of the dynamic voltage restorer (DVR) in an optimal manner in order to improve the fault‐ride‐through (FRT) capability of the grid‐connected doubly‐fed induction generators. An active crowbar protection (ACB_P) coupled with the rotor of the DFIG, provides a very little compensation, on blocking the high rotor current during fault condition. Control of DVR is achieved through use of multiple PI controllers. This paper presents a novel multi‐objective tuning known as Autonomous Group Particle Swarm Optimisation (AGPSO) to optimally tune the PI controllers. The optimisation algorithm uses diverse autonomous groups confined within a common target to achieve more directed and randomised search results for any population. Voltage sag compensation, total harmonic distortion (THD), RMS value of signal are the three major indices for comparison study during fault. Finally, the performance improvement in FRT of the DFIG with optimised controller was studied through DFIG responses on comparing with normal controller. Efficacy of the proposed controller proposed is verified by a simulation model of DFIG System with 1.5 MW rating in MATLAB. The results are analysed and comparative data are placed to ensure the enhanced FRT capability of the system.